Ritmos em Performance: Análise métrica do Párodo de As Suplicantes de Ésquilo - Mota, Marcus (2020)
In this paper, I present the scansion and a preliminary analysis of the entrance of the choir in the scene in Aeschylus' The Supplices. The aim is to provide material for studies that take into account the relationship between text, metrics, and performance in the interpretation of works of ancient Athenian dramaturgy.